Preparation method of adsorbent
By preparing ZrFe-BC adsorbent, the problem of zirconia being easily lost during the absorption of SO42- is solved, and an efficient and economical sulfate ion removal effect is achieved, which significantly reduces the cost of wastewater treatment.
Patent Information
- Application Number
- CN202411743297.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-03-04
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Zirconia is easily lost during the absorption of SO42- and requires additional solid-liquid separation equipment, which increases operating cost and complexity.
A method of preparing adsorbent is adopted to obtain ginkgo leaves for pretreatment, pyrolysis, and grinding, and hydrothermal reaction with ZrOCl2·8H2O, FeCl3 and biochar to form ZrFe-BC adsorbent.
The removal of sulfate ions was achieved efficiently, with the removal rate of 93.16% for the first use, and the removal rate remained at 78.05% after 4 adsorption-regeneration cycles, significantly reducing the cost of wastewater treatment.
Smart Images

Figure CN119549112A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of sulfate removal, and in particular to a method for preparing an adsorbent. Background Art
[0002] At present, the removal of sulfate in mine water treatment mainly relies on ion exchange technology, especially the use of sulfate (SO4 2- ) Resins with selective adsorption. These resins are usually based on polymer materials and are spherical or granular. Their surfaces are modified with acidic or basic functional groups, which can fix and exchange anions or cations in water. The regeneration process of this type of resin only requires simple water washing to achieve the separation of the adsorbate and the reuse of the resin. When using a fixed bed resin filling method, there is no need to set up an additional backwashing process, thereby reducing the wear and breakage of the resin and reducing the complexity of the sulfate adsorption treatment.
[0003] However, high-performance ion exchange resins are expensive to prepare, with a price tag of tens of thousands of yuan per ton, which limits their application in large-scale wastewater treatment. To address this problem, new technologies such as the New Desulfation System (NDS) process developed by Kaneka Corporation of Japan achieve continuous and selective removal of SO4 from brine by utilizing the strong affinity of zirconium oxide (ZrO2) for sulfate. 2- The advantages of the NDS process are that it does not produce solid waste during operation, has low operating costs, is non-toxic, does not damage the metal anode and ion exchange membrane, and can accurately control SO4 in the water. 2- concentration, with good chlorine resistance, low salt loss and excellent filtration performance.
[0004] Although the NDS process shows significant advantages, zirconium oxide is easily lost during water treatment, which requires additional solid-liquid separation equipment to be added to the process flow, thereby increasing operating costs and complexity. In addition, the high cost and loss problem of zirconium oxide limit its application in large-scale wastewater treatment. Summary of the invention
[0005] The main purpose of the present invention is to provide a method for preparing an adsorbent to solve the problem of zirconium oxide in the prior art in absorbing SO4 2- The problem is that it is easy to lose during the process and requires additional solid-liquid separation equipment.
[0006] In order to achieve the above object, according to one aspect of the present invention, a method for preparing an adsorbent is provided, comprising:
[0007] Obtaining a first raw material, the first raw material is ginkgo leaves;
[0008] Pre-treating the first raw material to obtain a raw material to be processed;
[0009] Pyrolyzing the raw material to be processed to obtain a pyrolysis product;
[0010] grinding the pyrolysis product to obtain a grinding product;
[0011] Obtaining a second raw material, subjecting the second raw material to ultrasonic treatment, precipitating with an alkaline solution and stirring to obtain a mixed solution, passing the mixed solution and the polished product into a hydrothermal reactor for hydrothermal reaction to obtain a hydrothermal reaction product, and post-treating the hydrothermal reaction product to obtain an adsorbent, wherein the adsorbent is ZrFe-BC;
[0012] Among them, the second raw material is ZrOCl2·8H2O, FeCl3 and biochar, and the ratio of ZrOCl2·8H2O:FeCl3 is 7:3.
[0013] Further, the step of pyrolyzing the raw material to be processed includes:
[0014] Pyrolyzing the first raw material at a preset temperature for a set time to obtain a pyrolysis product;
[0015] Among them, the preset temperature is 700℃ and the set time is 6h.
[0016] Further, the step of polishing the pyrolysis product comprises:
[0017] The speed of the high energy ball mill was controlled to be 300 rpm and the ball milling time was 2 h;
[0018] The pyrolysis product is added to a high-energy ball mill for ball milling to obtain a milled product.
[0019] Further, the step of ultrasonically treating the second raw material comprises:
[0020] adding a second raw material into an ultrasonic cleaning device;
[0021] Deionized water was added to the ultrasonic cleaning apparatus and ultrasonic treatment was performed for 30 min.
[0022] Further, the step of precipitating with an alkaline solution and stirring to obtain a mixed solution comprises:
[0023] Adding the second raw material after ultrasonic treatment and 3 mol / L alkaline solution into a beaker, so that the second raw material after ultrasonic treatment and the alkaline solution undergo a chemical reaction to obtain a reaction product;
[0024] The reaction product was stirred at a rotation speed of 300 rpm for 60 min to obtain a mixed solution;
[0025] Wherein, the alkaline solution is 3 mol / L sodium hydroxide solution.
[0026] Further, the mixed solution and the polished product are introduced into a hydrothermal reaction kettle for hydrothermal reaction to obtain a hydrothermal reaction product.
[0027] Steps include:
[0028] Passing the mixed liquid and the polished product into a hydrothermal reaction kettle;
[0029] The hydrothermal temperature was controlled to be 125° C. and the hydrothermal reaction time was controlled to be 12 h to obtain a hydrothermal reaction product.
[0030] Furthermore, the step of post-treating the hydrothermal product to obtain an adsorbent comprises:
[0031] Centrifugally filtering the hydrothermal reaction product to obtain a centrifugation filtered product;
[0032] The centrifugal filtration product is washed with deionized water to obtain a washed product;
[0033] Drying the cleaned product to obtain an adsorbent;
[0034] The rotation speed when the hydrothermal reaction product is centrifugally filtered is 4000 rpm.
[0035] Furthermore, the centrifugal filtration product was washed 3 times with deionized water.
[0036] Further, the temperature for drying the cleaned product is 80° C.; and / or,
[0037] The environment for drying the cleaned product is a vacuum environment; and / or,
[0038] The drying time for the cleaned product is 24 hours.
[0039] The technical scheme of the present invention is applied. Ginkgo biloba is an easily available and free biomass material. It is pre-treated by washing and acid washing to effectively remove surface impurities, improve the efficiency of subsequent treatment and the purity of the adsorbent. The pre-treated ginkgo biloba is pyrolyzed at high temperature to be converted into biochar with a high specific surface area, and then ball milled to further increase the surface area of the material and improve the adsorption performance. By controlling the mass ratio of ZrOCl2·8H2O to FeCl3 to 7:3, ultrasonic treatment and precipitation reaction are used to uniformly load zirconium oxide and iron oxide on the surface of biochar, thereby enhancing the selective adsorption capacity of the adsorbent for sulfate. The biochar loaded with zirconium oxide and iron oxide is reacted with a specific mixed solution in a hydrothermal reactor to form a stable composite structure. After post-treatment of centrifugation, washing and drying, a ZrFe-BC adsorbent with high stability and high adsorption capacity is obtained.
[0040] According to the experimental results, the ZrFe-BC adsorbent not only has an excellent removal effect on sulfate ions, but its removal rate reached 93.16% when it was first used, which is significantly higher than that of traditional adsorbent materials. More importantly, the adsorbent has good regeneration performance. Even after 4 adsorption-regeneration cycles, its efficiency in removing sulfate ions remains at 78.05%, showing a strong ability to be reused, greatly reducing the cost of wastewater treatment. In addition, the ZrFe-BC adsorbent also has a removal effect on a variety of anions (such as PO4^3-), which indicates that it has a wide range of application potential in the treatment of complex water bodies. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0042] Figure 1 A flow chart showing the preparation method of an embodiment of the present application is shown;
[0043] Figure 2 The result of FTIR analysis of the biochar surface in the embodiment of the present application is shown;
[0044] Figure 3 The dosage of biochar in this embodiment of the present application has an effect on SO4 2- Effect diagram of removal rate;
[0045] Figure 4 The dosage of biochar in this embodiment of the present application has an effect on SO4 2- Influence diagram of adsorption effect;
[0046] Figure 5 This is a graph showing the effect of different pH values on the removal rate of sulfate adsorbed by biochar in an embodiment of the present application;
[0047] Figure 6 This is a graph showing the effect of different pH values on the sulfate adsorption capacity of biochar according to an embodiment of the present application. DETAILED DESCRIPTION
[0048] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.
[0049] The present application provides a method for preparing an adsorbent, comprising:
[0050] S1. Obtain a first raw material, the first raw material is ginkgo leaves;
[0051] S2, pre-treating the first raw material to obtain a raw material to be processed;
[0052] S3, pyrolyzing the raw material to be processed to obtain a pyrolysis product;
[0053] S4, grinding the pyrolysis product to obtain a grinding product;
[0054] S5, obtaining a second raw material, subjecting the second raw material to ultrasonic treatment, precipitating with an alkaline solution and stirring to obtain a mixed solution, introducing the mixed solution and the polished product into a hydrothermal reactor for hydrothermal reaction to obtain a hydrothermal reaction product, and post-treating the hydrothermal reaction product to obtain an adsorbent, wherein the adsorbent is ZrFe-BC;
[0055] Among them, the second raw material includes ZrOCl2·8H2O, FeCl3 and biochar, and the ratio of ZrOCl2·8H2O:FeCl3 is 7:3.
[0056] Specifically, Figures 1 to 6 The ginkgo leaf is an easily available and free biomass material. It is pre-treated by washing and acid washing to effectively remove surface impurities, improve the efficiency of subsequent treatment and the purity of the adsorbent. The pre-treated ginkgo leaf is pyrolyzed at high temperature to be converted into biochar with a high specific surface area, and then ball milled to further increase the surface area of the material and improve the adsorption performance. By controlling the mass ratio of ZrOCl2·8H2O to FeCl3 to 7:3, ultrasonic treatment and precipitation reaction are used to uniformly load zirconium oxide and iron oxide on the surface of biochar, thereby enhancing the selective adsorption capacity of the adsorbent for sulfate. The biochar loaded with zirconium oxide and iron oxide is reacted with a specific mixed solution in a hydrothermal reactor to form a stable composite structure. After post-treatment of centrifugation, washing and drying, a ZrFe-BC adsorbent with high stability and high adsorption capacity is obtained.
[0057] According to the experimental results, ZrFe-BC adsorbent not only has excellent removal effect on sulfate ions, but also has a removal rate of 93.16% when it is first used, which is significantly higher than that of traditional adsorbent materials. More importantly, the adsorbent has good regeneration performance. Even after 4 adsorption-regeneration cycles, its efficiency in removing sulfate ions remains at 78.05%, showing a strong ability to be reused, which greatly reduces the cost of wastewater treatment. In addition, ZrFe-BC adsorbent also has good removal effect on various anions (such as PO4 3- ), which indicates that it has wide application potential in complex water treatment.
[0058] The step of pre-treating the first raw material includes: washing the first raw material with water and acid to obtain the raw material to be treated;
[0059] The acid is 0.5 mol / L dilute hydrochloric acid.
[0060] Specifically, the ginkgo leaves were washed with water and acid (using 0.5 mol / L dilute hydrochloric acid) to remove dust, microorganisms and some organic matter on the surface, reduce the occupation of impurities on the adsorption sites, and thus improve the adsorbent for target ions (such as SO4 2- ) selectivity and adsorption efficiency.
[0061] During the pickling process, dilute hydrochloric acid reacts with certain components on the surface of ginkgo leaves, exposing more active sites and providing better binding conditions for the subsequent loading of zirconium oxide and iron oxide, thereby enhancing the surface activity and adsorption capacity of the adsorbent.
[0062] The pretreatment process helps to adjust the pore structure of the biochar formed after pyrolysis of ginkgo leaves, making it more suitable as a carrier for zirconium oxide and iron oxide. The optimization of this structure is crucial to improving the mechanical strength and stability of the adsorbent, and helps reduce the loss of materials due to wear and breakage during use.
[0063] Although pretreatment adds a step to the preparation process, it effectively reduces the cost and complexity of the subsequent treatment process by improving the purity and performance of the adsorbent. The low-cost nature of ginkgo leaves as raw materials, combined with the efficiency of pretreatment, makes the prepared ZrFe-BC adsorbent have significant advantages in terms of economy and practicality.
[0064] Using ginkgo leaves to prepare adsorbents not only solves the problem of agricultural and forestry waste disposal, but also realizes the recycling of resources, embodies the concepts of green chemistry and sustainable development, and has a positive role in promoting environmental protection and the realization of carbon neutrality goals.
[0065] Based on the above analysis, the pretreatment step of this proposal effectively improves the adsorption performance, regeneration ability and structural stability of the adsorbent, while maintaining the economical preparation cost, providing a new efficient and environmentally friendly way to remove sulfate from mine water. The adsorbent ZrFe-BC optimized by pretreatment can more stably adsorb and remove sulfate ions in practical applications, and still maintains a high adsorption efficiency after multiple regenerations, demonstrating its broad application prospects in the field of wastewater treatment.
[0066] Further, the step of pyrolyzing the raw material to be processed includes:
[0067] Pyrolyzing the first raw material at a preset temperature for a set time to obtain a pyrolysis product;
[0068] Among them, the preset temperature is 700℃ and the set time is 6h.
[0069] Specifically, under high temperature conditions of 700°C, the organic components in the ginkgo leaves cracked and carbonized, forming biochar with a high specific surface area and rich pore structure. This pore structure provides a large number of adsorption sites, enhancing the adsorption capacity of the adsorbent for sulfate ions. After a long period of high-temperature pyrolysis (6 hours), the biochar converted from ginkgo leaves has higher thermal and chemical stability, which means that during the wastewater treatment process, the adsorbent can better resist the erosion of various physical and chemical conditions and is not prone to performance degradation or structural damage.
[0070] High-temperature pyrolysis helps to increase the hydrophobicity of biochar, which is particularly important for using the adsorbent in water-rich environments. The hydrophobicity allows the adsorbent to more effectively contact sulfate ions in wastewater without being hindered by water molecules.
[0071] The biochar formed during the pyrolysis process has high surface activity and porosity, providing an ideal substrate for the subsequent loading of zirconium oxide and iron oxide. This loading process is more uniform and stable, which is conducive to improving the adsorption efficiency and reusability of the adsorbent.
[0072] Although the high-temperature pyrolysis process requires a certain amount of energy input, the performance of the adsorbent can be significantly improved by controlling the pyrolysis conditions (such as temperature and time), thereby reducing the subsequent processing costs and improving the overall economic benefits. After pyrolysis, ginkgo leaves are converted into high-value adsorption materials, turning waste into treasure and being environmentally friendly.
[0073] The biochar structure formed during the pyrolysis process has good regeneration performance. After adsorption-regeneration cycle experiments, the removal rate of sulfate ions by the adsorbent is still maintained at a high level even after multiple regenerations. This shows that the adsorbent has excellent regeneration ability and reuse potential, which reduces material consumption and reduces the overall cost of wastewater treatment.
[0074] The pore structure and surface chemistry of pyrolyzed biochar have been optimized to improve the selective adsorption of sulfate ions while reducing interference with other coexisting anions, enabling more precise control of the removal of target pollutants.
[0075] In summary, this proposal achieved efficient conversion of ginkgo leaves by pyrolysis at 700 °C for 6 h. The prepared ZrFe-BC adsorbent performed well in terms of structural stability, adsorption efficiency, regeneration ability and selectivity for coexisting anions, providing an economical, environmentally friendly and efficient solution for the removal of sulfate in mine water.
[0076] Further, the step of polishing the pyrolysis product comprises:
[0077] The speed of the high energy ball mill was controlled to be 300 rpm and the ball milling time was 2 h;
[0078] The pyrolysis product is added to a high-energy ball mill for ball milling to obtain a milled product.
[0079] Specifically, ball milling can effectively reduce the particle size of pyrolysis products and increase their specific surface area. High specific surface area is the key to efficient adsorption of adsorbent materials because it provides more surface sites for adsorbing sulfate ions, thereby significantly improving the adsorption capacity of the adsorbent. The ball milling process helps to refine and optimize the pore structure of pyrolysis biochar, making the pore size distribution more uniform and the pore channels more unobstructed, which helps the adsorbent to contact the sulfate ions in the wastewater more fully and enhances the adsorption efficiency. Although ball milling will reduce the particle size, the rotation speed of 300 rpm and the ball milling time of 2 hours can avoid excessive crushing, while making the internal structure of the material more compact, improving the mechanical strength and wear resistance of the adsorbent, and is conducive to maintaining structural stability and adsorption performance in practical applications.
[0080] The surface of the biochar after ball milling is smoother and more uniform, providing a more uniform contact surface for the subsequent loading of zirconium oxide and iron oxide, which helps to improve the uniformity of the chemical reaction, ensure the uniform distribution of zirconium oxide and iron oxide on the biochar, and enhance the overall performance of the adsorbent.
[0081] The refined particles and optimized pore structure facilitate the diffusion of substances in the adsorbent during the regeneration process, allowing sulfate ions to be released more thoroughly from the adsorbent, thereby improving the regeneration efficiency and the adsorption performance after regeneration, extending the service life of the adsorbent and reducing the overall cost of wastewater treatment.
[0082] The smaller particle size and optimized pore structure improve the fluidity and packing performance of the adsorbent in practical applications, facilitate uniform distribution in the reactor, and improve operational simplicity and processing efficiency.
[0083] The ball milling process may have changed the surface chemical properties of biochar, further enhancing the selective adsorption capacity for sulfate ions, while reducing the nonspecific adsorption of other coexisting anions, and improving the application effect in complex water bodies.
[0084] In summary, by controlling the rotation speed of the high-energy ball mill to 300 rpm for 2 hours of ball milling treatment, the ZrFe-BC adsorbent prepared in this application has been significantly optimized in terms of specific surface area, pore structure, mechanical properties, chemical reaction uniformity, regeneration performance and operating characteristics. These technical effects jointly improve the efficiency and economy of the adsorbent in the removal of sulfate ions in mine water, and provide a more efficient, environmentally friendly and cost-effective method for preparing adsorption materials for the wastewater treatment field.
[0085] Further, the step of ultrasonically treating the second raw material comprises:
[0086] adding a second raw material into an ultrasonic cleaning device;
[0087] Deionized water was added to the ultrasonic cleaning apparatus and ultrasonic treatment was performed for 30 min.
[0088] Further, the step of precipitating with an alkaline solution and stirring to obtain a mixed solution comprises:
[0089] Adding the second raw material after ultrasonic treatment and 3 mol / L alkaline solution into a beaker, so that the second raw material after ultrasonic treatment and the alkaline solution undergo a chemical reaction to obtain a reaction product;
[0090] The reaction product was stirred at a rotation speed of 300 rpm for 60 min to obtain a mixed solution;
[0091] Wherein, the alkaline solution is 3 mol / L sodium hydroxide solution.
[0092] Specifically, ultrasonic treatment can effectively disperse the particles of the second raw material (ZrOCl2·8H2O, FeCl3 and biochar) in deionized water and prevent agglomeration, thereby ensuring the uniformity of the subsequent coprecipitation reaction. This uniformity is crucial to the performance of the adsorbent because it affects the efficiency and stability of the combination of zirconium oxide and iron oxide with biochar.
[0093] The introduction of ultrasound can accelerate the chemical reaction in the solution because ultrasound can generate local high temperature and high pressure, thereby reducing the activation energy of the chemical reaction, making the co-precipitation reaction of ZrOCl2·8H2O and FeCl3 in NaOH solution faster and more efficient. This not only shortens the preparation time, but also improves the energy efficiency of the adsorbent preparation process.
[0094] Ultrasonic treatment helps to clean and activate the surface of the second raw material, making the binding sites of zirconium oxide and iron oxide with biochar more active, enhancing the surface activity of the material and helping to improve the adsorption capacity for sulfate ions.
[0095] Through the mechanical effect of ultrasound, the pore structure of biochar can be optimized, the pore size distribution can be more reasonable, and the porosity can be improved. This optimized pore structure is conducive to the contact between the adsorbent and the ions in the wastewater, thus improving the adsorption efficiency.
[0096] Ultrasonic treatment can effectively reduce defects such as bubbles and uneven precipitation that may occur during the co-precipitation process, ensure the uniformity and stability of the internal structure of the adsorbent, and thus improve its performance in practical applications.
[0097] Ultrasonic treatment helps to form a more stable composite material structure, reduces the loss of zirconium oxide and iron oxide during the regeneration process, improves the stability and regeneration ability of the adsorbent, and enables the ZrFe-BC adsorbent to maintain a high adsorption performance after multiple adsorption-regeneration cycles, thereby reducing the operating cost of wastewater treatment.
[0098] The optimized material structure and surface activity enable the ZrFe-BC adsorbent to more effectively and selectively adsorb sulfate ions when treating wastewater containing multiple anions, while reducing the nonspecific adsorption of other anions, thereby improving the selectivity and efficiency in the treatment of complex water bodies.
[0099] In summary, by treating in an ultrasonic cleaning device for 30 minutes, this proposal not only accelerates the chemical reaction process of adsorbent preparation, but also significantly optimizes the structure, surface activity and stability of the ZrFe-BC adsorbent, improves the adsorption efficiency and selectivity of sulfate ions, and ensures the regeneration performance and economy in practical applications, providing a more efficient and environmentally friendly adsorbent preparation technology for mine water treatment.
[0100] Further, the mixed solution and the polished product are introduced into a hydrothermal reactor for hydrothermal reaction to obtain a hydrothermal reaction product, which comprises:
[0101] Passing the mixed liquid and the polished product into a hydrothermal reaction kettle;
[0102] The hydrothermal temperature was controlled to be 125° C. and the hydrothermal reaction time was controlled to be 12 h to obtain a hydrothermal reaction product.
[0103] Specifically, under hydrothermal conditions, zirconium oxide and iron oxide are more firmly bonded to biochar to form a stable composite structure, which provides more active sites for the adsorption of sulfate ions and significantly enhances the adsorption capacity of the adsorbent.
[0104] During the hydrothermal reaction, the high temperature and high pressure environment promoted the refinement and optimization of the biochar pores, forming a more uniform and richer pore structure, which was conducive to the rapid diffusion and deep adsorption of sulfate ions and improved the adsorption efficiency.
[0105] The hydrothermal temperature of 125°C can ensure the complete chemical reaction while avoiding the decomposition of materials that may be caused by excessively high temperatures. The products of the reaction under this condition have good chemical stability, are not prone to secondary reactions during wastewater treatment, and reduce the possible generation of by-products. The materials that have undergone hydrothermal reactions are more stable in physical structure, which reduces the wear and breakage that may occur in practical applications, is conducive to the long-term use of the adsorbent, and reduces the replacement frequency and cost. The ZrFe-BC adsorbent prepared under hydrothermal reaction conditions has a strong regeneration ability. Even after multiple adsorption-regeneration cycles, the decrease in its adsorption performance is small, and it can maintain a high adsorption efficiency and reduce the treatment cost. Under hydrothermal conditions, the reaction rate is accelerated and the purity of the product is also improved. This is because the high temperature and high pressure environment promotes the full contact and reaction of the reactants, and also helps the decomposition and discharge of by-products. The hydrothermal reactor provides stable temperature and pressure conditions, making the reaction process easy to control and operate, which is conducive to the standardization and scale of industrial production processes, and improves production efficiency and output.
[0106] Compared with treatments at higher temperatures, the hydrothermal reaction temperature of 125°C reduces energy consumption and carbon emissions while ensuring the complete reaction, reflecting the environmental friendliness of the process.
[0107] In summary, the ZrFe-BC adsorbent prepared in this proposal was significantly improved in terms of adsorption capacity, pore structure, chemical stability, physical stability, regeneration performance, reaction rate, product purity, ease of operation and environmental protection through hydrothermal reaction at 125 °C for 12 hours, providing an efficient and environmentally friendly solution for the efficient removal of sulfate ions in mine water.
[0108] Furthermore, the step of post-treating the hydrothermal product to obtain an adsorbent comprises:
[0109] Centrifugally filtering the hydrothermal reaction product to obtain a centrifugation filtered product;
[0110] The centrifugal filtration product is washed with deionized water to obtain a washed product;
[0111] Drying the cleaned product to obtain an adsorbent;
[0112] The rotation speed when the hydrothermal reaction product is centrifugally filtered is 4000 rpm.
[0113] Specifically, the centrifugal filtration step is carried out at a speed of 4000rpm, which can effectively separate the precipitate generated in the hydrothermal reaction from the residual liquid, remove the residue that does not participate in the reaction and the possible by-products, significantly improve the purity of the adsorbent, and reduce the negative impact of impurities on adsorption performance. In the centrifugal filtration process, selecting an appropriate rotating speed (4000rpm) can ensure the structural integrity of the particles, avoid the particle crushing and pore structure destruction caused by the excessively high rotating speed, maintain the high specific surface area and good porosity of the adsorbent, and be conducive to the efficient adsorption of sulfate ions. The cleaning step uses deionized water, avoids the passivation or clogging of the surface active sites that may be caused by using water containing impurities, protects the active sites on the adsorbent surface, and ensures the efficient adsorption and selectivity of sulfate ions in wastewater treatment.
[0114] Removing tiny particles and residual chemicals through centrifugal filtration and washing helps to improve the mechanical and chemical stability of the adsorbent, allowing ZrFe-BC to maintain a high adsorption efficiency after long-term use and multiple regeneration cycles, reducing the operating cost of wastewater treatment.
[0115] Cleaning removes nonspecific adsorbed substances on the surface of the adsorbent, reduces additional chemical reactions during the regeneration process, makes it easier for the adsorbent to restore its initial adsorption performance during the regeneration process, and enhances its reuse and regeneration capabilities.
[0116] The centrifugal filtration, washing and drying process is simple and easy to operate, reducing the complexity of subsequent treatment. At the same time, the use of deionized water for washing avoids the possibility of introducing other harmful chemicals and improves the safety of the entire preparation process.
[0117] In summary, this proposal effectively removes impurities and protects the structural integrity and surface activity of the adsorbent through the post-treatment steps of centrifugal filtration, washing and drying, improves the purity, performance stability and regeneration ability of the ZrFe-BC adsorbent, and provides a preparation technology guarantee for the efficient and selective removal of sulfate ions in mine water. It also demonstrates good ease of operation and safety, which is conducive to industrial-scale production and application.
[0118] Furthermore, the centrifugal filtration product was washed 3 times with deionized water.
[0119] Cleaning with deionized water can effectively remove impurities such as reaction by-products, unreacted raw materials and possible inorganic salts remaining on the surface and pores of the adsorbent, ensuring the purity of the adsorbent and avoiding the influence of these impurities on subsequent adsorption performance.
[0120] Repeated cleaning can prevent residual substances from potentially damaging the adsorbent structure, such as the crystallization of certain salts that may block pores and affect adsorption efficiency. The cleaning process helps maintain the integrity of the material's pore structure, thereby optimizing its adsorption performance.
[0121] The cleaning process is also a surface treatment that removes the inert layer or contaminants on the surface, exposing and activating the active sites on the adsorbent surface, thereby enhancing its adsorption capacity and selectivity for sulfate ions.
[0122] Further, the temperature for drying the cleaned product is 80° C.; and / or,
[0123] The environment for drying the cleaned product is a vacuum environment; and / or,
[0124] The drying time for the cleaned product is 24 hours.
[0125] Specifically, the centrifugal filtration step is carried out at a rotation speed of 4000 rpm, which can effectively separate the precipitate generated in the hydrothermal reaction from the residual liquid, remove the residues that have not participated in the reaction and possible by-products, significantly improve the purity of the adsorbent, and reduce the negative impact of impurities on the adsorption performance.
[0126] Deionized water is used in the washing step, which avoids the passivation or clogging of surface active sites that may be caused by the use of water containing impurities, protects the active sites on the adsorbent surface, and ensures efficient adsorption and selectivity of sulfate ions in wastewater treatment.
[0127] Removing tiny particles and residual chemicals through centrifugal filtration and washing helps to improve the mechanical and chemical stability of the adsorbent, allowing ZrFe-BC to maintain a high adsorption efficiency after long-term use and multiple regeneration cycles, reducing the operating cost of wastewater treatment.
[0128] Cleaning removes nonspecific adsorbed substances on the surface of the adsorbent, reduces additional chemical reactions during the regeneration process, makes it easier for the adsorbent to restore its initial adsorption performance during the regeneration process, and enhances its reuse and regeneration capabilities.
[0129] The centrifugal filtration, washing and drying process is simple and easy to operate, reducing the complexity of subsequent treatment. At the same time, the use of deionized water for washing avoids the possibility of introducing other harmful chemicals and improves the safety of the entire preparation process.
[0130] The products can be quickly separated by centrifugal filtration, which reduces the time required to wait for natural precipitation. The washing and drying steps also help to speed up the subsequent processes, thereby improving the efficiency and capacity of adsorbent preparation overall.
[0131] In summary, this proposal effectively removes impurities and protects the structural integrity and surface activity of the adsorbent through the post-treatment steps of centrifugal filtration, washing and drying, improves the purity, performance stability and regeneration ability of the ZrFe-BC adsorbent, and provides a preparation technology guarantee for the efficient and selective removal of sulfate ions in mine water. It also demonstrates good ease of operation and safety, which is conducive to industrial-scale production and application.
[0132] like Figure 2 As shown in Figure 2, in order to study the functional groups on the surface of biochar, FTIR analysis was performed. Figure 2 It can be seen that the Zr-O stretching vibration of ZrO2 is generally located at a wavelength of 469 cm -1 At 1102cm -1 The typical absorption peak of CO is at 1339cm -1 The vibration of ZrO(OH)2 bond on the biochar surface is caused by the deformation vibration at 2923 cm -1 The aliphatic -CH2- at 3204cm -1 The -OH of alcohol / phenol and the OH stretching vibration of residual water on the biochar surface are at 873 cm -1 The absorption peak may be that of aromatic hydrocarbons. ZrFe-BC adsorbs SO4 2- After that, at 1051cm -1 The SO bond of sulfate appears at SO4 2- Appearing on the surface of ZrFe-BC means that the material successfully adsorbs sulfate. 3204cm -1 The absorption peak of -OH at the position becomes wider, the transmittance decreases, the number of -OH decreases and a blue shift of 15 cm occurs. -1 .1339cm -1 The -OH at the position deforms and vibrates, and the absorption peak weakens, and the number of -OH decreases, indicating that -OH and SO4 2- Replacement.
[0133] Analysis of the effect of dosage on SO4 2- The influence of adsorption effect;
[0134] Measure 100 mL of SO4 with an initial concentration of 300 mg / L into each of the 5 250 mL beakers. 2- The solution was then added with 0.25g, 0.5g, 1g, 2g, and 3g of zirconium-iron modified biochar adsorption material respectively; the beaker was sealed and placed in a magnetic stirring water bath for stirring, and samples were taken at specific time points; the water sample was filtered with a 0.45μm syringe filter, and its absorbance was measured after dilution to calculate SO4 2- concentration.
[0135] Figure 3 , Figure 4 The effect of biochar dosage on sulfate removal was shown in Figure 2. The dosages were 0.25g, 0.5g, 1g, 2g, and 3g. When the dosage of biochar increased from 0.25g to 1g, the removal rate of sulfate also increased from 22.083% to 75.301%. When the dosage reached 2g, the removal rate reached 99.986%. When the dosage increased from 2g to 3g, the removal rate did not increase, and the adsorption capacity decreased. After adding 2g, 500mg / L of sulfate was completely removed, and the sulfate concentration dropped to 0, but the adsorption capacity gradually decreased. When the dosage of biochar was 0.25g, the adsorption capacity was the highest. This is because with the increase in dosage, the active sites on the surface of the modified biochar were not maximized and were not adsorbed saturated. When the dosage was 0.25g, the 300mg / L sulfate solution reached below the emission limit. When the dosage is 0.5g, the 400mg / L sulfate solution can reach below the emission limit. When the dosage is 1g, the 500mg / L sulfate solution can reach below the emission limit. 0.5g was selected for subsequent experiments.
[0136] (2) pH and SO4 2- The influence of adsorption effect;
[0137] Take two series of 100mL of SO4 with an initial concentration of 300mg / L 2- The solution was placed in a 250 mL beaker, and the pH was adjusted to 3, 5, 7, 9, and 11 with 0.1 mol / L NaOH and HCl solutions. Then 0.5 g of zirconium-iron modified biochar adsorption material was added to the beaker. The beaker was sealed and placed in a magnetic stirring water bath for stirring. Samples were taken at specific time points. The water sample was filtered with a 0.45 μm syringe filter, and its absorbance was measured after dilution to calculate SO4 2- concentration.
[0138] Figure 5 , Figure 6 The effect of different pH values on the removal rate of sulfate adsorbed by biochar. As shown in the figure, under room temperature, when SO4 2- The initial concentration was 300 mg / L, the biochar dosage was 0.5 g, and after 2 hours of adsorption, the adsorption of sulfate by biochar increased with the decrease of pH. Proper control of pH has a great influence on the removal rate of sulfate by biochar. Under alkaline conditions, the concentration of sulfate does not decrease after adding biochar, and biochar has no adsorption effect on sulfate under alkaline conditions. This is because in acidic solutions, the hydroxyl groups on the surface of biochar are protonated, making it positively charged, which increases the removal rate of sulfate. However, in alkaline solutions, there are many negatively charged OH groups in the sulfate solution. - , competing with sulfate with the same negative charge. Due to the limited number of active sites on the biochar surface, most of them are used to adsorb OH- In addition, the hydroxyl groups on the surface of biochar will be deprotonated, which increases the repulsion of sulfate ions on the surface of modified biochar, thereby greatly reducing the removal rate of sulfate ions.
[0139] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit the exemplary embodiments according to the present application. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprise" and / or "include" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.
[0140] Unless otherwise specifically stated, the relative arrangement, numerical expressions and numerical values of the parts and steps set forth in these embodiments do not limit the scope of the present invention. Meanwhile, it should be understood that, for ease of description, the sizes of the various parts shown in the accompanying drawings are not drawn according to the actual proportional relationship. The technology, method and equipment known to those of ordinary skill in the relevant art may not be discussed in detail, but in appropriate cases, the technology, method and equipment should be considered as a part of the specification. In all examples shown and discussed here, any specific value should be interpreted as being merely exemplary, rather than as a limitation. Therefore, other examples of exemplary embodiments may have different values. It should be noted that similar reference numerals and letters represent similar items in the following drawings, and therefore, once a certain item is defined in an accompanying drawing, it does not need to be further discussed in subsequent drawings.
[0141] In the description of the present invention, it is necessary to understand that the directions or positional relationships indicated by directional words such as "front, back, up, down, left, right", "lateral, vertical, perpendicular, horizontal" and "top, bottom" are usually based on the directions or positional relationships shown in the drawings. They are only for the convenience of describing the present invention and simplifying the description. Unless otherwise specified, these directional words do not indicate or imply that the devices or elements referred to must have a specific direction or be constructed and operated in a specific direction. Therefore, they cannot be understood as limiting the scope of protection of the present invention. The directional words "inside and outside" refer to the inside and outside relative to the contours of each component itself.
[0142] For ease of description, spatially relative terms such as "above", "above", "on the upper surface of", "above", etc. may be used here to describe the spatial positional relationship between a device or feature and other devices or features as shown in the figure. It should be understood that spatially relative terms are intended to include different orientations of the device in use or operation in addition to the orientation described in the figure. For example, if the device in the accompanying drawings is inverted, the device described as "above other devices or structures" or "above other devices or structures" will be positioned as "below other devices or structures" or "below other devices or structures". Thus, the exemplary term "above" can include both "above" and "below". The device can also be positioned in other different ways (rotated 90 degrees or in other orientations), and the spatially relative descriptions used here are interpreted accordingly.
[0143] In addition, it should be noted that the use of terms such as "first" and "second" to limit components is only for the convenience of distinguishing the corresponding components. If not otherwise stated, the above terms have no special meaning and therefore cannot be understood as limiting the scope of protection of the present invention.
[0144] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing an adsorbent, characterized in that: include: Obtaining a first raw material, wherein the first raw material is ginkgo leaves; Pre-treating the first raw material to obtain a raw material to be processed; Pyrolyzing the raw material to be processed to obtain a pyrolysis product; grinding the pyrolysis product to obtain a grinding product; Obtaining a second raw material, subjecting the second raw material to ultrasonic treatment, precipitating with an alkaline solution and stirring to obtain a mixed solution, passing the mixed solution and the polished product into a hydrothermal reaction kettle for hydrothermal reaction to obtain a hydrothermal reaction product, and post-treating the hydrothermal reaction product to obtain the adsorbent, wherein the adsorbent is ZrFe-BC; Among them, the second raw material includes ZrOCl2·8H2O, FeCl3 and biochar, and the ratio of ZrOCl2·8H2O:FeCl3 is 7:
3.
2. The method for preparing an adsorbent according to claim 1, characterized in that: The step of pre-treating the first raw material comprises: Washing the first raw material with water and acid to obtain the raw material to be processed; Wherein, the acid is 0.5 mol / L dilute hydrochloric acid.
3. The method for preparing an adsorbent according to claim 1, characterized in that: The step of pyrolyzing the raw material to be processed comprises: Pyrolyzing the first raw material at a preset temperature for a set time to obtain the pyrolysis product; Wherein, the preset temperature is 700°C and the set time is 6 hours.
4. The method for preparing an adsorbent according to claim 1, characterized in that: The step of polishing the pyrolysis product comprises: The speed of the high-energy ball mill was controlled to be 300 rpm, and the ball milling time was 2 h; The pyrolysis product is added into the high energy ball mill for ball milling to obtain the milled product.
5. The method for preparing an adsorbent according to claim 1, characterized in that: The step of ultrasonically treating the second raw material comprises: adding the second raw material into an ultrasonic cleaning device; Deionized water was added to the ultrasonic cleaning device, and ultrasonic treatment was performed for 30 minutes.
6. The method for preparing an adsorbent according to claim 1, characterized in that: The step of precipitating with the alkaline solution and stirring to obtain the mixed solution comprises: Adding the second raw material after the ultrasonic treatment and the 3 mol / L alkaline solution into a beaker, so that the second raw material after the ultrasonic treatment reacts chemically with the alkaline solution to obtain a reaction product; Stirring the reaction product at a rotation speed of 300 rpm for 60 min to obtain the mixed solution; Wherein, the alkaline solution is 3 mol / L sodium hydroxide solution.
7. The method for preparing an adsorbent according to claim 1, characterized in that: The step of introducing the mixed solution and the polished product into a hydrothermal reaction kettle for hydrothermal reaction to obtain a hydrothermal reaction product comprises: Passing the mixed liquid and the polished product into the hydrothermal reaction kettle; The hydrothermal temperature was controlled to be 125° C. and the hydrothermal reaction time was controlled to be 12 h to obtain the hydrothermal reaction product.
8. The method for preparing an adsorbent according to claim 1, characterized in that: The step of post-treating the hydrothermal reaction product to obtain an adsorbent comprises: Centrifugally filtering the hydrothermal reaction product to obtain a centrifugation filtered product; Washing the centrifugal filtration product with deionized water to obtain a washed product; Drying the cleaned product to obtain the adsorbent; Wherein, the rotation speed when the hydrothermal reaction product is centrifugally filtered is 4000 rpm.
9. The method for preparing an adsorbent according to claim 8, characterized in that: The centrifugal filtration product was washed with deionized water three times.
10. The method for preparing an adsorbent according to claim 8, characterized in that: The temperature for drying the cleaned product is 80° C.; and / or, The environment for drying the cleaning product is a vacuum environment; and / or, The drying time for the cleaned product is 24 hours.